Metabolic Profiling of Resistant and Susceptible Tobaccos Response Incited by Ralstonia pseudosolanacearum Causing Bacterial Wilt - Yang, Liang; Wei, Zhouling; Valls, Marc; Ding, Wei (Frontiers in Plant Science, 2022)
The causal agent of bacterial wilt, Ralstonia pseudosolanacearum, can cause significant economic losses during tobacco production. Metabolic analyses are a useful tool for the comprehensive identification of plant defense response metabolites. In this study, a gas chromatography-mass spectrometry (GC-MS) approach was used to identify metabolites differences in tobacco xylem sap in response to R. pseudosolanacearum CQPS-1 in two tobacco cultivars: Yunyan87 (susceptible to R. pseudosolanacearum) and K326 (quantitatively resistant). Metabolite profiling 7 days post inoculation with R. pseudosolanacearum identified 88 known compounds, 42 of them enriched and 6 depleted in the susceptible cultivar Yunyan87, while almost no changes occurred in quantitatively resistant cultivar K326. Putrescine was the most enriched compound (12-fold) in infected susceptible tobacco xylem, followed by methyl-alpha-d-glucopyranoside (9-fold) and arabinitol (6-fold). Other sugars, amino acids, and organic acids were also enriched upon infection. Collectively, these metabolites can promote R. pseudosolanacearum growth, as shown by the increased growth of bacterial cultures supplemented with xylem sap from infected tobacco plants. Comparison with previous metabolic data showed that beta-alanine, phenylalanine and leucine were enriched during bacterial wilt in both tobacco and tomato xylem.